Security Simulations in Undergraduate Education: A Review - Joseph Simpson; Aaron Brantly (Journal of Cybersecurity Education, Research & Practice)
Several decades of research in simulation and gamification in higher education shows that simulations are highly effective in improving a range of outcomes for students including declarative knowledge and interest in the topic being taught. While there appears to be a broad array of options to provide education in an undergraduate setting related to security, no previous reviews have explored computer-based simulations covering all facets of security. Given the increasing importance and adoption of interdisciplinary educational programs, it is important to take stock of simulations as a tool to broaden the range of problems, perspectives, and solutions presented to students. Our review provides an overview of computer-based simulations in U.S. undergraduate institutions published in academic journals and conferences. We identify strengths and limitations of existing computer-based simulations as well as opportunities for future research.